Precision current measurement with thermal-drift-minimized offset current for single-parameter electron pumps based on gate-switching technique - Kim, Bum-Kyu; Park, Suk-In; Song, Jindong; Choi, Hyung-Kook; Kim, Wan-Seop; Kim, Nam; Bae, Myung-Ho (AMER INST PHYSICS, 2020)
Single-parameter single-electron pumps (SEPs) based on a quantum dot have been suggested as promising devices to realize the new definition of the unit of current, the ampere, where quantized current produced from the SEP device is only defined by the elementary charge e and applied external radiofrequency (rf), f, i.e., I = ef. The conventional method to eliminate offset signals in the precision current measurement of pump current has been to measure the current difference between the pump-on and pump-off states. To date, the rf-on and rf-off method has been used to pump between its on and off states. However, this method inevitably induces alternating rf-heating effects and varying temperatures of the device environment, possibly leading to a thermal drift of the offset current. In the current work, we developed a new gate-switching technique that can alternate the pump on and off states while maintaining a constant rf-on state, resulting in a more stable system temperature. Using the gate-switching technique, we achieved a temperature-stabilized environment and performed a precision current measurement with sub-parts per million uncertainty.